Determinan Perilaku Perawat dalam Pemberian Edukasi Pasien pada Rumah Sakit di Jakarta Selatan - Yetti, Krisna; Pratiwi, Laras Adythia; Gayatri, Dewi (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Nurse behavior has a strong influence on the need and trust of patient education which identifiesdeterminants of nurse behavior in presenting patient education with a cross sectional design. The studyused total sampling with 210 samples according to the inclusion criteria. The instrument used was amodification of various literature reviews which tested its validity and reliability. The majority of nurseshave the following characteristics: female, <35 years old, not attending D3 Nursing, having totalexperience <10 years, civil servant status, having attended training (in the last three years), but lackingknowledge related to providing patient education . There is a relationship between age, policies, policies,working conditions, supervision, social support, and the planning function of the head of the room with thebehavior of nurses in providing patient education (p = 0.001-0.037), the most dominant variable affectingthe behavior of nurses in providing patient education is support. social (OR = 5,186). Nursing managersand the ranks of the hospital need to create a support program to offer patient education, complete allexisting facilities and infrastructure, as well as prepare competent resources.